Menyelidiki Hubungan antara Citra Merek, Brand Ambassador, dan Keputusan Pembelian Pemutih Wajah Scarlett: Peran Mediasi dari Kepercayaan Pelanggan - Kusuma Dewi, Intan; Komariyatin, Nurul (DINASTI RESEARCH, 2025)
In addition to having a large market potential, Indonesia's cosmetics industry is also one of the industrial sectors that many domestic industry players are involved in because it can compete with various brands abroad. This makes competition tougher and encourages cosmetic companies, especially local producers, to be able to stand out in the eyes of potential consumers so that potential consumers end up with a decision to transact with a particular company and become its customers. This study aims to determine the effect of brand ambassadors and brand image on purchase decisions for scarlett whitening products mediated by customer trust. This study uses PLS-SEM as an analysis technique and is processed using SmartPLS software version 4.0. The results of the analysis show that: Based on the data above, the conclusion that can be drawn is that the results of the analysis show that the Brand Ambassador and Brand Image variables more strongly influence the Purchase Decision variable with Customer Trust as the Intervening variable.